2022
DOI: 10.3390/bios12110977
|View full text |Cite
|
Sign up to set email alerts
|

Eu-Chelate Polystyrene Microsphere-Based Lateral Flow Immunoassay Platform for hs-CRP Detection

Abstract: Inflammation caused by viral or bacterial infection is a major threat to human health globally. Blood C-reactive protein (CRP) has been proven to be a sensitive indicator for the occurrence and development of inflammation. Furthermore, a tiny change of blood CRP concentration may portend chronic diseases; therefore, high-sensitivity CRP (hs-CRP) detection in a quantitative, rapid, user-friendly, and low-cost manner is highly demanded. In this paper, we developed a europium-chelate polystyrene microsphere (EuPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Polystyrene is a widely used commercial thermoplastic polymer [ 184 , 185 ]. Polystyrene is usually made from styrene monomer.…”
Section: Implication Of Polymer/fullerene Nanocomposite Membranes In ...mentioning
confidence: 99%
“…Polystyrene is a widely used commercial thermoplastic polymer [ 184 , 185 ]. Polystyrene is usually made from styrene monomer.…”
Section: Implication Of Polymer/fullerene Nanocomposite Membranes In ...mentioning
confidence: 99%
“…Many factors can influence the diffusion effect of fluorescent molecules during swelling, and Sun et al 16 obtained a fluorescent microsphere with high luminous intensity by optimizing swelling parameters such as swelling agent, swelling temperature, swelling time, compound doping amounts, etc. Li et al 17 enhanced the performance of Eu( iii )-based microspheres through adjusting the density of antibodies on the microspheres based on the swelling method. Wang et al 18 demonstrated that the integration of an evaporation step into the swelling method facilitates the diffusion and migration of fluorescent molecules into the interior of microspheres, thereby enhancing luminous intensity.…”
Section: Introductionmentioning
confidence: 99%